Determinants of Rural Outmigration in India - Chimankar, Digambar Abaji (Economic Journal of Nepal, 2014)
Migration, the process of changing places from one geographical area to another, is more complex demographic phenomena of population change than fertility and mortality.The process is part and parcel of the human civilization. The present study, Bhandara district in Maharashtra, India is not exception to this phenomenon. The main objective of the study is to look into the determinants and patterns of migration in the district of Bhandara. From the different economic, social and demographic backgrounds, male and female both are migrating for marriage, education and employment. Female are migrating because of marriage and male migrating because of employment. The patterns of migration show that rural to rural to rural migration is more than the urban. It is dominated because of the marriage migration. Male migrants are migrating towards the urban places because of unemployment. Ever married, highly educated, low standard of living persons are migrating more irrespective of their caste, religion and type of family.